Planting Healthy Roots: Using Documentary Film to Evaluate and Disseminate Community-Based Participatory Research. Issue 4 (October 2016) - Brandt, Heather M.; Freedman, Darcy A.; Friedman, Daniela B.; Choi, Seul Ki; Seel, Jessica S.; Guest, M. Aaron; Khang, Leepao
Abstract : Documentary filmmaking approaches incorporating community engagement and awareness raising strategies may be a promising approach to evaluate community-based participatory research. The study purpose was 2-fold: (1) to evaluate a documentary film featuring the formation and implementation of a farmers' market and (2) to assess whether the film affected awareness regarding food access issues in a food-desert community with high rates of obesity. The coalition model of filmmaking, a model consistent with a community-based participatory research (CBPR) approach, and personal stories, community profiles, and expert interviews were used to develop a documentary film ( Planting Healthy Roots ). The evaluation demonstrated high levels of approval and satisfaction with the film and CBPR essence of the film. The documentary film aligned with a CBPR approach to document, evaluate, and disseminate research processes and outcomes.